Toward the Next Frontiers of Vibrational Bioimaging - Haomin Wang; Dongkwan Lee; Lu Wei (Chemical & Biomedical Imaging, 2023)
Chemical imaging based on vibrational contrasts can extract molecular information entangled in complex biological systems. To this end, nonlinear Raman scattering microscopy, mid-infrared photothermal (MIP) microscopy, and atomic force microscopy (AFM)-based force-detected photothermal microscopies are emerging with better chemical sensitivity, molecular specificity, and spatial resolution than conventional vibrational methods. Their utilization in bioimaging applications has provided biological knowledge in unprecedented detail. This Perspective outlines key methodological developments, bioimaging applications, and recent technical innovations of the three techniques. Representative biological demonstrations are also highlighted to exemplify the unique advantages of obtaining vibrational contrasts. With years of effort, these three methods compose an expanding vibrational bioimaging toolbox to tackle specific bioimaging needs, benefiting many biological investigations with rich information in both label-free and labeling manners. Each technique will be discussed and compared in the outlook, leading to possible future directions to accommodate growing needs in vibrational bioimaging.